2021
DOI: 10.1093/rpd/ncab127
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Assessment of Occupational Exposure to Radon in Above-Ground Workplaces

Abstract: Representative sampling of radon in indoor air is difficult because the concentration often exhibits unpredictable spatial and temporal variation. In workplaces, temporal variation may be rapid, and the minimum and maximum concentration can differ by a factor of 100. In this paper, we compare methods for assessing the radon concentration in workplaces utilising the results of an initial investigation with a track-etch detector and the results of an additional continuous measurement. The recommended method is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Very close response times were observed at decreasing activity concentration. These values are in agreement with the values reported by [5], who observed that an hour after injection of radon activity, the RadonEye recorded (79 ± 3)% of the true radon concentration and after two hours (96 ± 4) %. The results show that RadonEye monitors could be successfully used for monitoring of the diurnal radon variations even in workplaces with part-time operation.…”
Section: Monitorsupporting
confidence: 93%
See 1 more Smart Citation
“…Very close response times were observed at decreasing activity concentration. These values are in agreement with the values reported by [5], who observed that an hour after injection of radon activity, the RadonEye recorded (79 ± 3)% of the true radon concentration and after two hours (96 ± 4) %. The results show that RadonEye monitors could be successfully used for monitoring of the diurnal radon variations even in workplaces with part-time operation.…”
Section: Monitorsupporting
confidence: 93%
“…This tendency for non-linearity was observed for all studied RadonEyes with respect to both the AlphaGUARD and the RAD7. Non-linearity in the signal of RadonEye Plus2 monitors has already been noted by [5]. A possible reason for the non-linearity is deadtime in the signal processing of the RadonEye monitors, although no data on it is provided by the producer.…”
Section: Linearity and Reproducibility Of The Radoneyesmentioning
confidence: 99%
“…Ventilation correction factor. The value of the ventilation correction factor according to eqn (1) was determined from the gross data of the RadonEye instrument read and processed at STUK (Turtiainen et al 2021). The number of data sets was 334.…”
Section: Estimation Of Radon Concentrations and Analysis Of The Datamentioning
confidence: 99%
“…Based on the previously reported results of this study, the best precision and accuracy in estimating the annual mean radon concentration during working hours is achieved when both integrated and continuous measurements are used (Turtiainen et al 2021). This method was applied here to estimate the occupational radon concentrations to which workers throughout Finland are exposed.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 99%
“…During these tests, the RadonEye +2 (RE) electronic radon detectors (2) demonstrated excellent sensitivity to 222 Rn and quick temporal response, which outlined them as good candidates to be tried out in campaigns for continuous 222 Rn monitoring. This type of detector has been preferred also for improving the assessment of indoor exposure to radon in workplaces (3).…”
mentioning
confidence: 99%